Concept of Branding in General: An Analysis of Customers’ Perspective - Shahriar Al Imran; Sayak Sarkar (International Journal of Engineering and Management Research, 2020)
When the word brand comes to mind, we, as a customer, can only think about those names which have created an impact in our mind. We do not keep those brand names in our mind which are not impactful. At the same time, it is a major concern for the brands to captivate the place in customers’ minds so that while making a purchase, customers can choose without having second thoughts. The concept of branding is very important in today’s globalized market, as there are lots of competitors in every field. It is the duty and responsibility of the top management of a company to maintain its brand image. But often they fail to do so due to lack of copy testing and customer behavior analysis. Furthermore, it is also important to know about customers’ perception on the concept ‘branding.’ This paper deals particularly with the perception of customers on the concept of branding. Researchers quantitatively analyzed the data collected from a survey to make conclusions which will help the managers to have an insight before making marketing strategies.